2018
DOI: 10.1080/1331677x.2018.1436457
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corporate governance on bank risk during a financial crisis

Abstract: Using agency theory, we explore the relationship between corporate governance mechanisms and bank risk. We employ panel data analysis to study the 97 largest European listed banks between 2006 and 2010, thereby covering the most recent international financial crisis. The results show that corporate governance mechanisms influence bank risk. During the financial crisis, different governance mechanisms can minimise or accentuate the agency conflict between shareholders and managers. In our model, bank size and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 41 publications
5
23
0
Order By: Relevance
“…The relationship found between board size and distance to default suggests that the risk of bankruptcy is positively and significantly related to the size of the board of directors. This result is in line with the work of Switzer et al (2018), Fel ıcio et al (2018, John and Ogechukwu (2018) and Baklouti et al (2016). All other boardrelated variables do not show a significant relationship to the risk of default.…”
Section: Introductionsupporting
confidence: 93%
“…The relationship found between board size and distance to default suggests that the risk of bankruptcy is positively and significantly related to the size of the board of directors. This result is in line with the work of Switzer et al (2018), Fel ıcio et al (2018, John and Ogechukwu (2018) and Baklouti et al (2016). All other boardrelated variables do not show a significant relationship to the risk of default.…”
Section: Introductionsupporting
confidence: 93%
“…due to the increased scrutiny of accounting practices. Facts such as weak investors' rights protection can provide insiders with incentives to extract private benefits by disguising the actual performance of the company (Fel ıcio et al, 2018;La Porta et al, 2000) and by obfuscating firm performance (Dick et al, 2017;Lee, Chen, & Ning, 2017;Leuz et al, 2003). The S.O.X.…”
Section: Institutional System and Real Activities Manipulationmentioning
confidence: 99%
“…Such a person is spared by procedural delays and unnecessary objections in making better decisions for organizational well-being. Recently, Felício et al [2018] reported a negative association between CEO duality and firm risk. Armeanu et al [2017] also supported these results as they found a negative relationship between CEO duality and failure risk, but their results were insignificant.…”
Section: Literature Review and Hypothesis Development 21 Board Vigilmentioning
confidence: 99%